2020
DOI: 10.1002/hep.31110
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of Cholangiocarcinoma in Primary Sclerosing Cholangitis Reveals Therapeutic Opportunities

Abstract: BaCKgRoUND aND aIMS: Lifetime risk of biliary tract cancer (BTC) in primary sclerosing cholangitis (PSC) may exceed 20%, and BTC is currently the leading cause of death in patients with PSC. To open new avenues for management, we aimed to delineate clinically relevant genomic and pathological features of a large panel of PSC-associated BTC (PSC-BTC). appRoaCH aND ReSUltS: We analyzed formalin-fixed, paraffin-embedded tumor tissue from 186 patients with PSC-BTC from 11 centers in eight countries with all anatom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 35 publications
6
55
0
Order By: Relevance
“…Furthermore, authors pointed out that anatomical site did not affect molecular subtypes nor patients’ prognosis in their cohort, since Clusters 1 and 2 comprised intrahepatic and extrahepatic tumors, while intrahepatic tumors were included in all 4 clusters. This observation, consistent with other studies [ 32 ], suggested that tumors from different anatomical site may have common molecular features, while sharing the same anatomical location does not imply molecular uniformity. Moreover, authors underlined the difficulty of merging data from multiple heterogenous cohorts and different sequencing platforms, that hampers also inter-study comparison.…”
Section: Cca Molecular Landscapesupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, authors pointed out that anatomical site did not affect molecular subtypes nor patients’ prognosis in their cohort, since Clusters 1 and 2 comprised intrahepatic and extrahepatic tumors, while intrahepatic tumors were included in all 4 clusters. This observation, consistent with other studies [ 32 ], suggested that tumors from different anatomical site may have common molecular features, while sharing the same anatomical location does not imply molecular uniformity. Moreover, authors underlined the difficulty of merging data from multiple heterogenous cohorts and different sequencing platforms, that hampers also inter-study comparison.…”
Section: Cca Molecular Landscapesupporting
confidence: 93%
“…As far as PSC is concerned, genomic and transcriptomic studies included a low percentage of patients with this condition, although it represents a predominant risk factor for CCA in Western world. To overcome this limitation, 186 PSC-BTCs tissue specimens from 11 centers in Europe and U.S. were recently analyzed by Goeppert et al [ 32 ], who established histological, molecular and etiological correlations within PSC-BTCs. Remarkably, samples were homogeneous in terms of histological pattern independently from anatomical location, being characterized by a large duct phenotype as previously observed [ 33 ].…”
Section: Cca Molecular Landscapementioning
confidence: 99%
“…220 Bankov et al 221 [222][223][224][225] Also in PSC-CCA, potentially actionable molecular targets were identified, including ERBB2, EGFR, MET, and MYC. 199 However, clinical data of targeted therapy in PSC-CCA is scarce.…”
Section: Mutation Profilingmentioning
confidence: 99%
“…6 CCA arising from PSC may have a distinct morphomolecular phenotype irrespective of anatomical location. 7 Despite improved outcomes associated with active CCA screening in PSC, 8 guideline recommendations remain controversial due to a lack of therapeutic options. 6 Finally, concurrent inflammatory bowel disease (IBD) in those with PSC confers additional CCA risk.…”
Section: Introductionmentioning
confidence: 99%